A DNA prime/protein boost vaccine protocol developed against Campylobacter jejuni for poultry. Issue 16 (12th April 2018) - Meunier, Marine; Guyard-Nicodème, Muriel; Vigouroux, Estelle; Poezevara, Typhaine; Béven, Véronique; Quesne, Ségolène; Amelot, Michel; Parra, Alberto; Chemaly, Marianne; Dory, Daniel
Abstract: Vaccination of broilers is one of the potential ways to decrease Campylobacter intestinal loads and therefore may reduce human disease incidence. Despite many studies, no efficient vaccine is available yet. Using the reverse vaccinology strategy, we recently identified new vaccine candidates whose immune and protective capacities need to be evaluated in vivo . Therefore, the goal of the present study was to develop and evaluate an avian subunit vaccine protocol for poultry against Campylobacter jejuni . For this, flagellin was used as vaccine antigen candidate. A DNA prime/protein boost regimen was effective in inducing a massive protective immune response against C. jejuni in specific pathogen free Leghorn chickens. Contrastingly, the same vaccine regimen stimulated the production of antibodies against Campylobacter in conventional Ross broiler chickens harbouring maternally derived antibodies against Campylobacter, but not the control of C. jejuni colonization. These results highlight the strength of the vaccine protocol in inducing protective immunity and the significance of the avian strain and/or immune status in the induction of this response. Nevertheless, as such the vaccine protocol is not efficient in broilers to induce protection and has to be adapted; this has been done in one of our recent published work.